Impact of RSV test positivity, patient characteristics, and treatment characteristics on the cost of hospitalization for acute bronchiolitis in a French university medical center (2010–2015) - Dervaux, Benoit; Van Berleere, Marine; Lenne, Xavier; Wyckaert, Marine; Dubos, François (Frontiers in Pediatrics, 2023)
Background: In young children, respiratory syncytial virus (RSV)-related bronchiolitis is typically more severe than other respiratory tract infections, with a greater need for oxygen therapy and respiratory support. Few studies have compared the cost of hospitalization with regard to virological status. The objective of this study was to compare the costs of hospitalization in a French university medical center between 2010 and 2015 for RSV-positive vs. RSV-negative bronchiolitis. Methods: Cost models were compared using conventional goodness-of-fit criteria. Covariates included the patients’ characteristics, pre-existing respiratory and non-respiratory comorbidities, superinfections, the medical care provided, and the length of stay. Results: RSV was detected in 679 (58.3%) of 1164 hospital stays by children under 2 with virological data. Oxygen therapy and respiratory support were twice as frequent for RSV-positive cases. The median hospitalization cost was estimated to €3248.4 (interquartile range: €2572.1). The cost distribution was positively skewed with a variation coefficient (CV = standard deviation/mean) greater than one (mean = €4212.9, standard deviation = €5047, CV = 1.2). In univariate analyses, there was no significant cost difference between RSV-positive and RSV-negative cases. In the best multivariate model, the significant positive effect of RSV positivity on cost waned after the introduction of medical care variables and the length of stay. The results were sensitive to the model’s specification. Conclusions: It was impossible to conclude firmly that hospitalization costs were higher for RSV-positive cases.